2011
DOI: 10.14507/epaa.v19n6.2011
|View full text |Cite
|
Sign up to set email alerts
|

High Expense: Disability Severity and Charter School Attendance in Arizona

Abstract: Much of the literature related to the skimming or cropping of students by charter schools has ignored special education students. This article examines the relationship between the severity of student disabilities and their likelihood of having attended an Arizona charter school in the 2002-2003 school year. After adjusting for student traits, local education agency characteristics, and the mix of available special education services, a multilevel logistic regression analysis suggests that students who had mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…This is not only the case in CPS. Garcy (2011) found that, in Arizona, students with severe disabilities were less likely to attend charter schools and those "students with more severe disabilities who were enrolled in charter schools were on average less expensive than those students enrolled in TPS [neighborhood schools]" (p. 19). On the other hand, differences found between grade levels in the proportions of students with ID and SI (see Table 3) indicate that the hypothesis of cropping off services for SRSE has stronger support at the elementary school level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not only the case in CPS. Garcy (2011) found that, in Arizona, students with severe disabilities were less likely to attend charter schools and those "students with more severe disabilities who were enrolled in charter schools were on average less expensive than those students enrolled in TPS [neighborhood schools]" (p. 19). On the other hand, differences found between grade levels in the proportions of students with ID and SI (see Table 3) indicate that the hypothesis of cropping off services for SRSE has stronger support at the elementary school level.…”
Section: Discussionmentioning
confidence: 99%
“…Five main conclusions can be drawn from examining research on the enrollment of SRSE in charter schools. First, the bulk of this research has been disseminated through policy reports sponsored by think tanks and state agencies, while a very small number of studies have been published in peer-reviewed journals (Garcy, 2011). Think tanks tend to be polarized on the issue of charter schools with those in support often receiving funding from foundations that support charter schools expansion (e.g., Gates Foundation; Walton Foundation).…”
Section: Research On the Enrollment Of Srse In Charter Schoolsmentioning
confidence: 99%
“…The author used a multilevel logistic regression analysis adjusting for student and school district characteristics, and available special education services in the district. Garcy (2011) found, among other demographic differences, that charter schools in Arizona enrolled significantly lower proportions of students with more severe and expensive disabilities than NS. Similarly, Wilkens (2011) studied the special education enrollment in the 2009-2010 school year in Massachusetts’s urban charter schools.…”
Section: Institutional Theory and Charter Schools Researchmentioning
confidence: 87%
“…Studies at the state and city level, using more sophisticated statistical methods, confirm national-level findings. Garcy (2011) conducted a study in Arizona with data from the 2002-2003 school year. The author used a multilevel logistic regression analysis adjusting for student and school district characteristics, and available special education services in the district.…”
Section: Institutional Theory and Charter Schools Researchmentioning
confidence: 99%
“…Despite the growth of charter schools, research on students with dis/abilities attending such schools has been limited in breadth and depth (Garcy, 2011;Waitoller, Maggin, & Trzaska, in press). This limited research has mostly been published in non-peer-reviewed outlets (e.g., reports from think tanks, governmental, and advocacy groups) and has presented contradictory findings.…”
Section: School Choice or The Politics Of Desperation? Black And Latimentioning
confidence: 99%